Practical medical applications of quantitative MR relaxometry - Margaret Cheng, Hai-Ling; Stikov, Nikola; Ghugre, Nilesh R.; Wright, Graham A. (Journal of magnetic resonance imaging, 2012)
Conventional MR images are qualitative, and their signal intensity is dependent on several complementary contrast mechanisms that are manipulated by the MR hardware and software. In the absence of a quantitative metric for absolute interpretation of pixel signal intensities, one that is independent of scanner hardware and sequences, it is difficult to perform comparisons of MR images across subjects or longitudinally in the same subject. Quantitative relaxometry isolates the contributions of individual MR contrast mechanisms (T1, T2, T2*) and provides maps, which are independent of the MR protocol and have a physical interpretation often expressed in absolute units. In addition to providing an unbiased metric for comparing MR scans, quantitative relaxometry uses the relationship between MR maps and physiology to provide a noninvasive surrogate for biopsy and histology. This study provides an overview of some promising clinical applications of quantitative relaxometry, followed by a description of the methods and challenges of acquiring accurate and precise quantitative MR maps. It concludes with three case studies of quantitative relaxometry applied to studying multiple sclerosis, liver iron, and acute myocardial infarction. J. Magn. Reson. Imaging 2012;36:805–824. © 2012 Wiley Periodicals, Inc.